The duty of medical practitioners and CAM/TCM practitioners to inform competent adult patients about alternatives - Zhao, Xiju (Springer Berlin Heidelberg Imprint Springe, 2013)
The book pays interest to a small and almost untouched topic: a health practitioner' s duty to inform about alternatives. It covers both orthodox medicine practitioners and CAM practitioners. The topic is explored in a co mparative way, examining the laws of not only common law jurisdictions, such as the USA, England, Canada, Australia, New Zealand, but also two East Asia jurisdictions ( China and Japan ) . It uses the collective wisdom of several common law jurisdictions, but also differentiates them. It places the issue of "disclosure of alternatives" in a clear and wider context, making a cogent distinction between diagnosis/treatment and information disclosure.